Intestinal microbial diversity in female rhesus (Macaca mulatta) at different physiological periods - Li, Yanyan; Yang, Fengmei; Chen, Lixiong; Duan, Suqin; Jin, Weihua; Liu, Quan; Xu, Hongjie; Zhang, Wei; Li, Yongjie; Wang, Junbin; He, Zhanlong; Zhao, Yuan (Frontiers in Microbiology, 2022)
To explore the physiology of female rhesus monkeys by measuring microbial composition of fecal samples during the menstrual cycle and identify their inter-relationship. Blood and fecal samples were collected from 6 female adult rhesus monkeys during the menstrual period (MP), ovulation period, and Luteal period (LP). Serum estradiol (E2) and progesterone (P) levels were determined by the chemiluminescence method and the stool samples were subjected to high-throughput 16S rRNA sequencing. The highest level of E2 and P secretions were during the MP, and LP, respectively. Stool samples produced valid sequences and the number of operation classification units/OUT was: 810056/3756 (MP), 845242/4159 (OP), 881560/3970 (LP). At the phylum level, the three groups of Firmicutes and Bacteroides accounted for >95%. The dominant flora at the LP was Bacteroides (53.85%), the dominant flora at the MP and OP was Firmicutes, 64.08 and 56.53%, respectively. At the genus level, the dominant genus at the LP was Prevotella, the dominant genera at the MP were Prevotella, Oncococcus, Streptococcus, and Kurtella. The dominant genera at OP were Prevotella and Nocococcus. At the phylum level, P levels were negatively correlated to Firmicutes, Actinomycetes Actinobacteria, and Fibrobacteres, but positively correlated to Bacteroidetes. Likewise, E2 was positively correlated to Proteobacteria but negatively correlated to Euryarchaeota. At the genus level, P hormone showed a significant correlation with 16 bacterial species, and E2 was significantly correlated to 7 bacterial species. Function prediction analysis revealed a high similarity between the MP and OP with 6 differentially functional genes (DFGs) between them and 11 DFGs between OP and LP (P<0.05). Fecal microbiota types of female rhesus monkeys varied with different stages of the menstrual cycle, possibly related to changes in hormone levels.